2015
DOI: 10.1177/0829573515601005
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Implementation of Check-In, Check-Out

Abstract: Check-In, Check-Out (CICO) is one of the most widely implemented Tier 2 behavior interventions in a school-wide system of Positive Behavior Interventions and Supports (PBIS). Much literature has documented implementation of CICO across individual schools or districts. The Illinois PBIS Network, currently known as the Midwest PBIS Network, has provided extensive training and technical assistance (TA) on CICO with more than 400 schools in more than 125 districts. The purpose of this descriptive study was to deta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…One of the most commonly implemented Tier 2 behavioral intervention in schools is Check-in/check-out (CICO; Hawken et al, 2021). CICO is a multicomponent intervention designed to teach students self-regulation skills (i.e., self-monitoring, self-assessment, goal setting, self-recruited feedback) to improve positive behaviors (e.g., academic engagement) and reduce challenging behavior (e.g., off-task, disruption).…”
Section: Check-in/check-out In Schoolsmentioning
confidence: 99%
“…One of the most commonly implemented Tier 2 behavioral intervention in schools is Check-in/check-out (CICO; Hawken et al, 2021). CICO is a multicomponent intervention designed to teach students self-regulation skills (i.e., self-monitoring, self-assessment, goal setting, self-recruited feedback) to improve positive behaviors (e.g., academic engagement) and reduce challenging behavior (e.g., off-task, disruption).…”
Section: Check-in/check-out In Schoolsmentioning
confidence: 99%
“…Their lessons included (a) Maintaining consistency with staff, (b) Assigning responsibilities judiciously and following through, and (c) Having an organized, efficient system for collecting and synthesizing data. Hawken et al ( 2015 ) also noted that schools with high CICO fidelity supported twice as many elementary and middle school students as schools with low CICO fidelity.…”
Section: Check-in/check-out As a Tier 2 Interventionmentioning
confidence: 99%
“…Research has demonstrated that implementation of CICO with fidelity is key to achieving desired outcomes. Although fidelity is generally between 70 and 90% in published research studies with oversight and involvement by researchers (Hawken et al, 2015 ; Hawken et al, 2015 ), adoption and fidelity are dependent on several issues and implementation can be uneven in typical school settings (Myers & Briere, 2010 ; Rodriguez, Campbell, Falcon, & Borgmeier, 2015 ). One variable relevant to implementation is the delineation and conveyance of specific practice elements that represent the concrete actions that expected implementers are to perform to deliver CICO with fidelity.…”
Section: Introductionmentioning
confidence: 99%
“…Tier 2 groups typically focus on students developing or improving skills and practicing those skills in a group setting with feedback from school staff and peers (Debnam et al, 2012; Goodman-Scott et al, 2023). Commonly implemented Tier 2 group supports include Check In/Check Out (CICO; Hawken et al, 2021) and school-counselor-led psychoeducational and counseling groups (Berger, 2013; McCormac, 2015; Rose & Steen, 2015). In both CICO and school-counselor-led groups, school counselors and the Tier 2 team use data to monitor progress and to make decisions to continue, modify, or fade supports based on students’ growth in goal areas (Hawken et al, 2021; see Todd et al, 2021, for progress monitoring guideline example).…”
Section: Group Supports Within Tier 2 Of the Mtss Frameworkmentioning
confidence: 99%